Peran Guru Terhadap Kesulitan Belajar Siswa dalam Pelaksanaan Pembelajaran Tematik di SD Negeri Siluk Bantul - Prasetia, Ryska Bayu; Mulyono, Rahmat (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to describe the role of teachers in overcoming students' learning difficulties in thematic learning at Silu Elementary School, students' learning difficulties experienced during thematic learning and teacher management in solving problems. This research method uses a descriptive qualitative research approach. With data collection techniques through participant observation, in-depth interviews and documentation. The informants for this research were school principals and class teachers related to thematic learning. Analyze the data using triangulation techniques. Data analysis uses data reduction, data display, and drawing conclusions. The results of research on the role of teachers in overcoming students' learning difficulties in thematic learning at Siluk Elementary School are (1) the causes of learning difficulties are lack of concentration and difficulty in remembering thematic learning material for a long time, (2) thematic learning as a learning model in elementary schools has various characteristics or characteristics. typical, namely students as the center of learning or what is often called (Student Centered education), learning is flexible, learning is comprehensive or holistic and meaningful, learning is tailored to students' interests and needs, provides direct experience, requires students to be active and eliminates dividing boundaries between subjects, and (3) The teacher's role in overcoming learning difficulties in thematic learning is as a facilitator whose task is to provide guidance and training to students so that changes occur